High-temperature-resistant antioxidant X-waveband total-absorption SiBCN-ZrO2 ceramic composite material and preparation method thereof
By preparing SiBCN-ZrO2 ceramic composite, the problems of insufficient wave absorption performance and poor oxidation resistance at high temperatures are solved, and the broad-spectrum electromagnetic wave absorption and high-temperature oxidation resistance are improved. It is suitable for stealth applications of components such as high Mach number aircraft.
Patent Information
- Application Number
- CN202510109752.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing PDC-SiBCN ceramics lack wave absorption performance and poor oxidation resistance at high temperatures, making it difficult to meet the high-temperature stealth needs of components such as high-Mach number aircraft.
By mixing liquid polyborosilazane and polyacetylacetonate evenly, performing low-temperature curing and high-temperature cracking heat treatment, SiBCN-ZrO2 ceramic composite material was prepared to enhance its dielectric loss ability and electromagnetic wave absorption performance.
It significantly improves the effective absorption bandwidth of SiBCN-ZrO2 ceramic composite material to 4.2GHz, covers the entire X band, and improves its high-temperature oxidation resistance and resistance, and is suitable for high-temperature stealth applications.
Smart Images

Figure CN119822845A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wave absorbing materials, and specifically relates to a SiBCN-ZrO2 ceramic composite material which is resistant to high temperature and oxidation and fully absorbs in the X-band, and a preparation method thereof. Background Art
[0002] Absorbing materials are widely used in stealth technology. High-temperature stealth technology is one of the key technologies for modern aircraft to move towards high Mach numbers, and is a very important technology to improve the survivability and penetration capabilities of aircraft. The application of absorbing materials is one of the important ways to achieve radar stealth function. In the hot end parts of aircraft, such as the surface of hypersonic aircraft, the nose cone cap of cruise missiles, the front edge of the wing and other components, the operating temperature is high and in a dynamic thermal environment such as oxidation, the reflection of radar waves is strong. With the increase of the Mach number of aircraft, the requirements for the ability of these components to withstand high temperature and harsh environments are getting higher and higher, requiring stealth materials to have excellent high-temperature absorbing, anti-oxidation, and thermal shock resistance. As a high-temperature resistant ceramic, PDC-SiBCN still has excellent thermal, chemical and mechanical stability when it is resistant to temperatures as high as 2000~2200 ℃ in an inert atmosphere. However, it is still amorphous at high temperatures and has poor absorbing performance. Therefore, how to improve the absorbing performance and high-temperature oxidation resistance of PDC-SiBCN-based ceramics is urgently needed.
[0003] Reference 1 "Luo C, Tang Y, Jiao T, et al. High-temperature stable and metal-free electromagnetic wave-absorbing SiBCN ceramics derived from carbon-rich hyperbranched polyborosilazanes [J]. ACS applied materials&interfaces, 2018, 10(33): 28051-28061." discloses that high-temperature stable, metal-free, and high electromagnetic wave absorbing efficiency silicon boron carbonitride ceramics were obtained by structural design and cracking of a carbon-rich branched polyborosilazanes precursor with pendant phenyl groups. The results show that the ceramics cracked from the pre-ceramic precursor containing benzene rings have a higher carbon content and more sp2 carbon, and in situ generate crystalline carbon (graphitic carbon and tubular carbon), which has considerable conductivity and therefore has good wave absorbing performance. The electromagnetic wave absorption efficiency and effective absorption bandwidth (EAB, reflection coefficient (RC)) of the ceramic can be adjusted by the heat treatment temperature. The ceramics stable at 1320 °C showed the best electromagnetic wave absorption performance, with a minimum RC of -71.80 dB and an EAB of 3.65 GHz. However, its electromagnetic wave absorption bandwidth is narrow, and the in-situ generated sp2 Carbon has poor high temperature resistance and oxidation resistance, and its practical application capabilities are weak.
[0004] Reference 2 "Liu H, Zhang Y, Liu X, et al. Additive manufacturing of nanocellulose / polyborosilazane derived CNFs-SiBCN ceramic metamaterials for ultra-broadband electromagnetic absorption[J]. Chemical Engineering Journal, 2022, 433: 133743." discloses a method of combining additive manufacturing technology and polymer-derived ceramic process to prepare defect-rich carbon nanofiber (CNFs) modified SiBCN ceramic-based metamaterials. Defect-rich CNFs were generated in situ by introducing nanocellulose into the pre-ceramic body through thermal cracking. When the cellulose content is 6.0 wt % and the annealing temperature is 1200 ℃, the real and imaginary parts of the dielectric constant can reach 17.0 and 7.0, respectively. The Cole-Cole circle plot shows that CNFs-SiBCN ceramics have strong polarization ability due to their defect-rich structure. At a thickness of 1.8 mm, the minimum RC can reach −20.0 dB and the EAB can reach 2.85 GHz. However, CNFs will lose their fiber structure under 400 °C oxidation conditions, and the effective absorption bandwidth at room temperature is narrow, which limits their application in the field of high-temperature oxidation absorption. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a SiBCN-ZrO2 ceramic composite material with high temperature resistance, oxidation resistance and full X-band absorption and a preparation method thereof. The present invention can solve the problem of narrow PDC-SiBCN absorption bandwidth and improve its high temperature resistance and oxidation resistance.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material comprises the following steps: Mixing liquid polyborosilazane and zirconium polyacetylacetonate uniformly to obtain a mixture A; the volume ratio of the liquid polyborosilazane and zirconium polyacetylacetonate is (1-2):1; Curing the mixture A in a protective atmosphere to obtain a cured block; Processing the solidified block into powder to obtain a powder of prefabricated ceramic sheet SiBCN-ZrO2; Pressing the powder of the prefabricated ceramic sheet SiBCN-ZrO2 into a shape to obtain a prefabricated ceramic sheet; The preformed ceramic sheet is subjected to high-temperature cracking heat treatment in a protective atmosphere to obtain the high-temperature resistant, oxidation-resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material.
[0007] Preferably, liquid polyborosilazane and polyzirconium acetylacetonate are uniformly mixed by mechanical stirring at 55-65° C. to obtain mixture A.
[0008] Preferably, when the mixture A is cured in a protective atmosphere, the curing temperature is 200-300° C. and the curing time is 1-3 hours.
[0009] Preferably, after the solidified block is processed into powder, it is sieved to obtain a powder of prefabricated ceramic sheet SiBCN-ZrO2 with a mesh size of 100-400.
[0010] Preferably, the solidified block is processed into powder by ball milling, and the rotation speed during ball milling is 40-60 rpm and the time is 5-12 hours.
[0011] Preferably, when the powder of the prefabricated ceramic sheet SiBCN-ZrO2 is pressed into shape, the pressure is 5-15 kPa.
[0012] Preferably, when the preform ceramic sheet is subjected to high-temperature cracking heat treatment in a protective atmosphere, the preform ceramic sheet is heated to 1100~1300°C at a heating rate of 2~5°C / min, and then occasionally kept warm for 1~3h. After the insulation is completed, it is cooled with the furnace to obtain the SiBCN-ZrO2 ceramic composite material that is resistant to high temperature and oxidation and has full X-band absorption.
[0013] Preferably, argon is used as the protective atmosphere.
[0014] The present invention also provides a SiBCN-ZrO2 ceramic composite material that is resistant to high temperature and oxidation and fully absorbs in the X-band. The SiBCN-ZrO2 ceramic composite material that is resistant to high temperature and oxidation and fully absorbs in the X-band is prepared by the above-mentioned preparation method.
[0015] Preferably, the reflection coefficient (RC) of the high temperature resistant and oxidation resistant SiBCN-ZrO2 ceramic composite material with full absorption in the X-band is at least -34.8 dB, and the effective absorption bandwidth (EAB) is 4.2 GHz.
[0016] The present invention has the following beneficial effects: The present invention mixes the liquid precursor of SiBCN (i.e. liquid polyborosilazane) and the liquid precursor of ZrO2 (i.e. polyacetylacetonate zirconium) uniformly, and prepares the SiBCN-ZrO2 ceramic composite material by low-temperature crosslinking and high-temperature pyrolysis. The composite material is based on PDC-SiBCN ceramic and combined with ZrO2 to form a composite material containing amorphous BN, Si3N4, SiO2 and sp 2 Multiphase ceramic composite material of carbon and ZrO2. The addition of ZrO2 phase enhances the dielectric loss capacity of PDC-SiBCN. The presence of each amorphous phase increases the impedance matching between the material and the electromagnetic wave free space, and improves the overall electromagnetic wave absorption capacity of the material. At the same cracking temperature, the minimum reflection coefficient of ZrO2-enhanced PDC-SiBCN is -34.8dB. Compared with 2.85GHz of CNFs-doped SiBCN, the effective absorption bandwidth (EAB) of the present invention is increased to 4.2GHz. In addition, the SiBCN-ZrO2 composite ceramic prepared by the present invention not only has the full X-band effective absorption bandwidth, but also has excellent high temperature resistance and oxidation resistance, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] FIG1 (a) is a scanning electron microscope photograph of the SiBCN-ZrO2 ceramic composite material obtained in Example 1 of the present invention; FIG1( b ) is a scanning electron microscope photograph of the SiBCN-ZrO2 ceramic composite material described in Example 2 of the present invention; FIG1( c ) is a scanning electron microscope photograph of the SiBCN-ZrO2 ceramic composite material obtained in Example 3 of the present invention; Figure 2 This is a transmission electron microscope photo of the SiBCN-ZrO2 ceramic composite material obtained in Example 3 of the present invention; Figure 3 This is a diagram of the microwave absorption performance of the SiBCN-ZrO2 ceramic composite material prepared in Example 3 of the present invention; Figure 4 The thermogravimetric graphs of the SiBCN-ZrO2 ceramic composite materials obtained in Examples 1 to 3 (corresponding to S1, S2 and S3) of the present invention under oxidation conditions of 20-1400°C. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] Most carbon materials used as absorbers face oxidation failure problems in high temperature environments. Zirconia, as an oxide ceramic material, has not only high temperature stability but also excellent performance in oxidative environments. The present invention selects ZrO2 ceramics as the wave absorbing and anti-oxidation reinforcement phase of PDC-SiBCN ceramics, in order to improve the wave absorbing bandwidth and high temperature anti-oxidation ability of PDC-SiBCN ceramics.
[0020] The present invention provides a SiBCN-ZrO2 ceramic composite material that is resistant to high temperature and oxidation and fully absorbs in the X-band and a preparation method thereof. First, polymer liquid phase precursors of SiBCN and ZrO2 are uniformly mixed, followed by low temperature curing and high temperature cracking heat treatment, and finally a SiBCN-ZrO2 composite ceramic material is obtained. The SiBCN-ZrO2 ceramic composite material prepared by the present invention can not only improve the insufficient loss capacity of PDC-SiBCN ceramics as absorbing materials and the narrow effective absorption bandwidth, but also improve the overall high temperature resistance and oxidation resistance of the material.
[0021] Specifically, the preparation method of the high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material of the present invention comprises the following steps: Step 1: Select liquid polyborosilazane (PSNB) and polyzirconium acetylacetonate (PZO) as polymer-converted ceramic precursors, and mechanically mix PSNB:PZO in a volume ratio of (1-2):1; during mechanical mixing, magnetically stir at 55-65°C for 2-4 hours to mix evenly to obtain a mixture A; use a heat treatment furnace with a resistance wire as a heating element, in an argon atmosphere, to cure the mixture A at 200-300°C for 1-3 hours to obtain a cured block.
[0022] Step 2: Use a planetary ball mill to ball mill the solidified block obtained in step 1, with a rotation speed of 40-60 rpm and a time of 5-12 hours. Sieve the milled powder to obtain a 100-400 mesh uniformly distributed prefabricated ceramic sheet SiBCN-ZrO2 powder.
[0023] Step 3: The SiBCN-ZrO2 ceramic powder prepared in step 2 is transferred to a stainless steel mold with a cavity size of 35×20×60 mm, and the powder is pressed into a preform ceramic sheet of a fixed size using a dry press at a pressure of 5-15 kPa. After demolding, a preform ceramic sheet is obtained.
[0024] Step 4: Place the pressed preformed ceramic sheet into a heat treatment furnace with a resistance wire as the heating element. In a flowing Ar atmosphere, increase the furnace temperature from room temperature to 1100-1300°C at a heating rate of 2-5°C / min and keep it warm for 1-3 hours. Turn off the power and cool it naturally to room temperature to obtain a heat-treated SiBCN-ZrO2 ceramic composite material.
[0025] Embodiment 1: The preparation method of the high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material of this embodiment comprises the following steps: (1) PSNB and PZO liquid precursors were mixed in a volume ratio of 1:1, heated and stirred at 60 °C on a magnetic stirrer for 3 h, and then the mixed liquid precursors were transferred into a heat treatment furnace with a resistance wire as a heating element. The precursor solution was cured at 280 °C for 2 h in an Ar atmosphere.
[0026] (2) Using a planetary ball mill, the solidified precursor obtained in step (1) was ball milled at a speed of 40 rpm for 12 h. The ball milled powder was sieved to obtain a prefabricated ceramic sheet SiBCN-ZrO2 powder with a uniform distribution of 100-400 mesh.
[0027] (3) Pour the powder of SiBCN-ZrO2 into a mold with a cavity size of 35×20×60 mm, and use a dry press to press the powder into a preform ceramic sheet of a fixed size at a pressure of 15 kPa.
[0028] (4) The pressed preform ceramic surface is placed in a heat treatment furnace with a resistance wire as the heating element. In a flowing Ar atmosphere, the furnace temperature is increased from room temperature to 1100°C at a heating rate of 5°C / min and kept at this temperature for 3 h. The power is turned off and the preform is naturally cooled to room temperature to obtain the SiBCN-ZrO2 composite ceramic after heat treatment.
[0029] Referring to FIG. 1 (a), it can be seen from the scanning electron microscope photograph of the SiBCN-ZrO2 ceramic composite material obtained in this example that the ceramic surface is dense and uniform; the thermogravimetric results of the SiBCN-ZrO2 ceramic composite material obtained in Example S1 under 20-1400°C oxidation conditions are as follows: Figure 4 As shown, it can be seen that the weight loss rate of the ceramic composite material after oxidation is 16.3%.
[0030] Embodiment 2: The preparation method of the high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material of this embodiment comprises the following steps: (1) PSNB and PZO liquid precursors were mixed in a volume ratio of 1:1, heated and stirred at 55 °C on a magnetic stirrer for 4 h, and then the mixed liquid precursors were transferred into a heat treatment furnace with a resistance wire as a heating element. The precursor solution was cured at 300 °C for 1 h in an Ar atmosphere.
[0031] (2) Using a planetary ball mill, the solidified precursor obtained in (1) was ball milled at a speed of 50 rpm for 10 h. The ball milled powder was sieved to obtain a prefabricated ceramic sheet SiBCN-ZrO2 powder with a uniform distribution of 100-400 mesh.
[0032] (3) Pour the powder of SiBCN-ZrO2 into a mold with a cavity size of 35×20×60 mm, and use a dry press to press the powder into a preform ceramic sheet of a fixed size at a pressure of 5 kPa.
[0033] (4) The pressed preform ceramic surface is placed in a heat treatment furnace with a resistance wire as the heating element. In a flowing Ar atmosphere, the furnace temperature is increased from room temperature to 1200°C at a heating rate of 2°C / min and kept at this temperature for 2 h. The power is turned off and the preform is naturally cooled to room temperature to obtain the SiBCN-ZrO2 composite ceramic after heat treatment.
[0034] Referring to FIG. 1( b ), it can be seen from the scanning electron microscope photograph of the SiBCN-ZrO2 ceramic composite material obtained in this example that the ceramic surface is dense and uniform; the thermogravimetric results of the SiBCN-ZrO2 ceramic composite material obtained in Example S2 under 20-1400° C. oxidation conditions are as follows: Figure 4 As shown, it can be seen that the weight loss rate of the oxidized ceramic composite material is 2.5%.
[0035] Embodiment 3: The preparation method of the high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material of this embodiment comprises the following steps: (1) PSNB and PZO liquid precursors were mixed in a ratio of 1:1, heated and stirred at 65 °C on a magnetic stirrer for 2 h, and then the mixed liquid precursors were transferred into a heat treatment furnace with a resistance wire as a heating element. The precursor solution was cured at 200 °C for 3 h in an Ar atmosphere.
[0036] (2) Using a planetary ball mill, the solidified precursor obtained in (1) was ball milled at a speed of 60 rpm for 5 h. The ball milled powder was sieved to obtain a prefabricated ceramic sheet SiBCN-ZrO2 powder with a uniform distribution of 100-400 mesh.
[0037] (3) Pour the powder of SiBCN-ZrO2 into a mold with a cavity size of 35×20×60 mm, and use a dry press to press the powder into a preform ceramic sheet of a fixed size at a pressure of 10 kPa.
[0038] (4) The pressed preform ceramic surface is placed in a heat treatment furnace with a resistance wire as the heating element. In a flowing Ar atmosphere, the furnace temperature is increased from room temperature to 1300°C at a heating rate of 4°C / min and maintained for 1 h. The power is turned off and the preform is naturally cooled to room temperature to obtain the heat-treated SiBCN-ZrO2 composite ceramic.
[0039] As shown in FIG1( c ), from the scanning electron microscope photo of the SiBCN-ZrO 2 ceramic composite material obtained in this embodiment, it can be seen that the ceramic surface is relatively dense; Figure 2 From the transmission electron micrograph of the SiBCN-ZrO2 ceramic composite material obtained in this example, it can be seen that the zirconium oxide phase is uniformly distributed in the amorphous SiBCN matrix; see Figure 3 From the wave absorption performance diagram of the SiBCN-ZrO2 ceramic composite material prepared in this embodiment, it can be seen that when the thickness is 3.8 mm, the effective wave absorption bandwidth of this sample covers the entire X-band; the thermogravimetric results of the SiBCN-ZrO2 ceramic composite material obtained in this embodiment S3 under 20~1400℃ oxidation conditions are as follows Figure 4 As shown, it can be seen that the weight gain rate of the oxidized ceramic composite material is 3.5%.
[0040] From the results of the above embodiments of the present invention, it can be seen that the ceramic composite material has an effective absorption bandwidth of 4.2 GHz in the X-band. Compared with 3.65 GHz of pure PDC-SiBCN ceramics, the effective absorption bandwidth is improved to cover the entire X-band, and the antioxidant ability is also improved.
[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material, characterized in that: The process includes the following: Mixing liquid polyborosilazane and zirconium polyacetylacetonate uniformly to obtain a mixture A; the volume ratio of the liquid polyborosilazane and zirconium polyacetylacetonate is (1-2):1; Curing the mixture A in a protective atmosphere to obtain a cured block; Processing the solidified block into powder to obtain a powder of prefabricated ceramic sheet SiBCN-ZrO2; Pressing the powder of the prefabricated ceramic sheet SiBCN-ZrO2 into a shape to obtain a prefabricated ceramic sheet; The preformed ceramic sheet is subjected to high-temperature cracking heat treatment in a protective atmosphere to obtain the high-temperature resistant, oxidation-resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material.
2. The method for preparing a high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material according to claim 1, characterized in that: Liquid polyborosilazane and polyzirconium acetylacetonate are uniformly mixed at 55-65° C. by mechanical stirring to obtain a mixture A.
3. The method for preparing a high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material according to claim 1, characterized in that: When the mixture A is cured in a protective atmosphere, the curing temperature is 200-300° C. and the curing time is 1-3 hours.
4. The method for preparing a high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material according to claim 1, characterized in that: The solidified block is processed into powder and then sieved to obtain a 100-400 mesh prefabricated ceramic sheet SiBCN-ZrO2 powder.
5. The method for preparing a high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material according to claim 1, characterized in that: The solidified block is processed into powder by ball milling, and the rotation speed is 40-60 rpm and the time is 5-12 hours during ball milling.
6. The method for preparing a high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material according to claim 1, characterized in that: When the powder of the prefabricated ceramic sheet SiBCN-ZrO2 is pressed into shape, the pressure is 5-15 kPa.
7. The method for preparing a high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material according to claim 1, characterized in that: When the preform ceramic sheet is subjected to high-temperature cracking heat treatment in a protective atmosphere, the preform ceramic sheet is heated to 1100-1300°C at a heating rate of 2-5°C / min, and then occasionally kept warm for 1-3 hours. After the insulation is completed, the preform ceramic sheet is cooled with the furnace to obtain the high-temperature resistant, oxidation-resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material.
8. The method for preparing a high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material according to claim 1, characterized in that: The protective atmosphere used was argon.
9. A SiBCN-ZrO2 ceramic composite material with high temperature resistance, oxidation resistance and X-band full absorption, prepared by the preparation method according to any one of claims 1 to 8.
10. The high temperature resistant, oxidation resistant and X-band fully absorbing SiBCN-ZrO2 ceramic composite material according to claim 9, characterized in that: The SiBCN-ZrO2 ceramic composite material which is resistant to high temperature and oxidation and fully absorbs in the X-band has a minimum reflection coefficient of -34.8 dB and an effective wave absorbing bandwidth of 4.2 GHz.
Citation Information
Patent Citations
Preparation method of high-temperature-resistant low-dielectric-loss SiBCN composite ceramic
CN117430427A